Vehicular Dragging Death: A Case Report (Indian Internet Journal of Forensic Medicine and Toxicology, 2026)
This case highlights the forensic importance of identifying injuries in cases of  prolonged vehicular dragging. A 27-year-old male motorcyclist died after being  trapped under a speeding limousine and dragged for nearly 11 km. The Re-postmortem  revealed extensive abraded lacerations, deep soft tissue loss, and exposed bones with  characteristics of “grinding/friction” injuries. Vital reaction was found in wounds over  the body. Internal findings showed craniocerebral injuries and long bone fractures.  These injury patterns helped to reconstruct the incident as a possible manslaughter  or homicide. This case highlights the medicolegal significance of re-postmortem  examination in clarifying manner of death in complex vehicular dragging incidents.
Keywords: Manslaughter; Dragging; Grinding; Bone Abrasion; Re Postmortem